Association of Carotid Atherosclerosis With White Matter Hyperintensity in an Asymptomatic Japanese Population: A Cross-Sectional Study - Zhang, Li; Zhou, Quan; Shao, Li Hua; Wen, Jun; Xia, Jun (Frontiers in Cardiovascular Medicine, 2021)
Objective: Evidence regarding the relationship between carotid atherosclerosis and Cerebral White matter hyperintensity (WMH) is limited and inconsistent, and the data analysis is not sufficient to clarify the true relationship between the two. We aimed to investigate the relationship between Carotid atherosclerosis and Cerebral White matter hyperintensity in an asymptomatic population in Japanese. Method: All participants underwent a medical health check-up program including a head MRI and ultrasonography of the carotid artery. The presence of WMH was diagnosed from their MRI results. The carotid ultrasound findings, carotid artery plaque score (PS), and plaque number（PN）was measured to reveal the severity of carotid atherosclerosis. Multivariable logistic regression models were used to estimate the association between carotid atherosclerosis and the presence of WMH. Interaction and stratified analyses were conducted according to age, sex, smoking status, drinking status, and histories of chronic disease. Results：A total of 1904 asymptomatic participants in Japanese was included, the prevalence of WMH was 54.8%(1044/1904). Carotid atherosclerosis was more pronounced in peoples with WMH. In a fully adjusted model, high PS was associated with the presence of WMH(adjusted OR 1.10, 95% CI 1.03 to 1.18) and followed by more PN(adjusted OR 1.21, 95% CI 1.07 to 1.38). Further analyses revealed a dose-response relationship between PS levels and incident WMH was observed, and the association also persisted in different subgroups. Conclusion: functional markers of carotid atherosclerosis (high PN and high PS on the carotid ultrasonography) have the most substantial impact on determining the presence of WMH, which suggests the potentially important pathophysiological role of large-artery atherosclerosis was involved in the development of WMH.